Effect of salinity on the biological treatment of wastewater from fish processing industry / Ching Yun Chen - Ching , Yun Chen (2017)
The fish processing industries produce large volumes of saline wastewater with high organic and nutrient concentrations. This research was aimed to study the effect of salt (NaCl) concentration on the biomass yield and biodegradation of fish processing wastewater in batch and continuous flow system by natural biodegradation. Three categories of synthetic wastewater were prepared according to random concentration which was diluted from the average concentration of fish processing wastewater; with the dilution at 30, 50 and 100 fold dilution. Each concentration of synthetic wastewater was later added with 12 series of salt concentration ranging from 0.0 g/L to 70.0 g/L of NaCl. All synthetic wastewater including the control were tested in the lab using 2.0 L bioreactor (oxygenated continuous stirred) with agitation speed at 250 rotation per minute (rpm) and operating temperature at 30oC. Studies were carried out using batch and continuous operation with a 5-day cycle treatment. In continuous flow system, the first phase of the experiments were focused towards the evaluation of system performance via evaluating biomass yield and substrate removal at 9 different operating hydraulic retention time (HRT) range of 2-10 day in the 30-, 50-, and 100-fold diluted wastewater without salt content in the reactor. The second phase of the experiments was to investigate the effects of eleven different salt content (NaCl: 0.5-7%) in the 30-, 50-, and 100-fold diluted wastewater at the obtained optimal HRT of 10, 9 and 8 day. In each run of continuous system, daily samples are taken at set time to analyze the concentration of biomass and substrates for study the biomass growth and substrate removal efficiency. Organic and nutrient removal together with biomass yield were used indicators for its performance efficiency. In the batch operation, the efficiency of substrate removal and biomass yield dropped at 2.5% NaCl for all types of synthetic fish processing wastewater. The efficiency of substrate removal and biomass yield dropped for continuous operation after 3.0% NaCl. The most efficient substrate removal and biomass yield took place at the salt concentration of 1.0% salt for batch and continuous operation in all types of synthetic fish processing wastewater. Continuous operation has shown that the longer hydraulic retention time (HRT) give the better efficiency of substrate removal up to 10-day HRT. Meanwhile for biomass yield, the HRT eight days has given the best results with 49.0% growth percentage found in the 30-fold diluted fish processing wastewater. The biomass yield and the substrate removal were decreased with bigger dilution factor of the diluted influent in both of the batch and continuous flow system. Results from this study could potentially increase fish processing saline wastewater handling and the treated wastewater reuse as an environmental friendly liquid fertilizer in agriculture, which is expected to yield high economic value.